Pencemaran dari Segi Logam di Sungai - Lidia Rahayu; Arman Harahap (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This research aims to determine metal pollution in the Marbau river basin in North Labuhanbatu Regency. Sampling was carried out at 3 monitoring points in the upstream to downstream areas of the Marbau River in North Labuhanbatu Regency. Determination of sample return points. The method used is purposive sampling, by determining sampling points based on the differences in characteristics found in the research area. Some of the parameters measured are temperature, conductivity, turbidity, total dissolved density, BOD, COD, DO, pH, nitrate and chlorophyll which are then compared with the Standard Criteria for Class III river water quality according to the attachment to the reference regulation PerMenKes No.32 of 2017. The research results show that the upstream to downstream areas of the Marbau River are areas that can be categorized as low level pollution referring to PP RI NO 82 TAHUN 2001 with the specified quality standard for the heavy metal lead being 0.003 ppm. The conclusion of the analysis of the heavy metal lead (PB) from upstream to downstream of the Marbau River shows that the heavy metal lead (PB) pollution in the river is still relatively low or has not been contaminated by the heavy metal lead (PB). Keywords: Labuhanbatu, Marbau, Water Pollution